Effect of Gamma Irradiation on Some Biochemical Components of Seed Extracts and Microbial Load of Fenugreek (Trigonella foenum-graecum L.) Seeds* - Musa, Hala A.A.; Ahmed, Eltayeb E.A.; Osman, Gammaa A.M.; Ali, Hiba A.; Müller, Jutta Ludwig- (University of Khartoum Journal of Agricultural Sciences, 2023)
The work was carried out to study the effects of gamma irradiation on microbial load and the content of some biochemical constituents of fenugreek (Trigonella foenum-graecum) seeds. It was conducted at the Department of Botany and Agricultural Biotechnology, Faculty of Agriculture, University of Khartoum and Institute of Botany, Technische Universität Dresden. Seeds were treated with gamma irradiation at the doses of 5, 10 and 15 kGy. Bacterial load was reduced from 1.44 x 106 , in untreated seeds, to 1.5 x 104 , 9.0 x 103 and 5.0 x 102 cfu/g, in seeds treated with5, 10 and 15 kGy, respectively. The stability of glycosides, phenols and tannins constituents of treated seeds was evaluated using thin layer chromatography (TLC) and high performance liquid chromatography (HPLC). The results of TLC analysis revealed that application of 15 kGy doses of gamma radiation to fenugreek seeds methanol-extract had no effect on glycosides patterns, and slight reduction in total phenol and increase in tannins content were observed. Analysis of methanol extractable compounds by HPLC revealed variations in the metabolite profile at different wavelengths after irradiation. While the content of several compounds increased slightly after gamma irradiation that of some decreased and some constituents showed no change. Accordingly, there were no major differences in chemical constituents between the irradiated and un-irradiated samples.